2002
DOI: 10.1007/s00049-002-8320-6
|View full text |Cite
|
Sign up to set email alerts
|

The roles of nicotine and natural enemies in determining larval feeding site distributions of Manduca sexta L. and Manduca quinquemaculata (Haworth) on tobacco

Abstract: Field observations indicated that hornworms select feeding sites non-randomly on tobacco. We tested the hypotheses that differences in feeding site locations of larvae of Manduca sexta L. and Manduca quinquemaculata (Haworth) (Lepidoptera: Sphingidae) on tobacco could be explained by differential nicotine concentrations within plants and leaves, species-specific responses to nicotine, or pressure exerted by natural enemies. Results showed that third-instar larvae of M. sexta fed more proximally and centrally o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Such behavior suggests that nicotine plays an important role in determining feeding sites of M. sexta larvae , as has been suggested in a study with cultivated tobacco (Kester et al 2002). While the relative toxic effects of anatabine and nicotine remain unstudied, these results are likely to underestimate the influence of nicotine on M.…”
Section: Resultssupporting
confidence: 55%
“…Such behavior suggests that nicotine plays an important role in determining feeding sites of M. sexta larvae , as has been suggested in a study with cultivated tobacco (Kester et al 2002). While the relative toxic effects of anatabine and nicotine remain unstudied, these results are likely to underestimate the influence of nicotine on M.…”
Section: Resultssupporting
confidence: 55%
“…Nicotine increased larval mortality and time to pupation and reduced pupal weight (data not shown); negative effects of nicotine on larval performance are consistent with previous studies (Bentz & Barbosa 1990;Appel & Martin 1992;Glendinning 2002;Kester et al 2002).…”
supporting
confidence: 91%
“…Shroff et al (2008) observed that larvae of the generalist Helicoverpa armigera avoided leaf margins and veins of A. thaliana rosette leaves. Herbivorous insects often consume specific parts of their host and have evolved recognition cues to avoid poisoncontaining areas and structural defenses or to select nutritious tissues (Kester et al, 2002;Schoonhoven et al, 2005). The nonuniform GS distribution could thus explain the feeding behavior of S. littoralis larvae, which avoided tissues with high GS contents, and that of P. brassicae larvae, which were attracted by GS-containing tissues.…”
Section: Discussionmentioning
confidence: 99%